Forms and Functions of Indonesian–English Code-Mixing on the YouTube Channel “Kok Bisa?”: A Digital Sociolinguistic Study - Ely Purwanti; Merry Lapasau; Samsinar Sambo; Putri Rahayu; Rifka Agustin (Journal of Language Development and Linguistics, 2026)
The development of digital media has transformed societal communication patterns, including the use of code-mixing between Indonesian and English. This study aims to describe the forms and functions of code-mixing in educational YouTube content. A qualitative descriptive method and digital sociolinguistic approach were applied, as the study examines the relationship between language use and the social context of digital communication in a bilingual society. Data were collected from 20 videos uploaded to the "Kok Bisa?" channel during January–June 2024 using non-participatory observation and note-taking techniques. Data analysis followed the Miles and Huberman model through stages of data reduction, data presentation, and conclusion drawing. The results yielded 126 code-mixing instances: word-form 72 (57%), phrase 39 (31%), clause 15 (12%). Code-mixing functions include communication effectiveness 48 (38%), closeness with Gen Z 35 (28%), modern identity 27 (21%), and emphasis of meaning in digital communication 16 (13%). The study found that code-mixing in educational YouTube content is functional and serves as a communication strategy in digital media.